2009
DOI: 10.1227/01.neu.0000335645.67282.03
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Guided Percutaneous Cordotomy for Intractable Pain in Malignancy

Abstract: In the treatment of intractable pain, CT-guided cordotomy is an option in specially selected cases with malignancy. In this study, anatomic and technical details of the procedure and the experience gained from treating 207 patients over a 20-year period are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
78
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 26 publications
0
78
1
3
Order By: Relevance
“…Kanpolat et al [10,29,30] described more than 200 patients with intractable pain with pulmonary carcinoma, mesothelioma and Pancoast tumours, and Yequl et al [15] described CT-guided percutaneous cordotomy as a useful procedure for the treatment of severe unilateral cancer pain syndromes. Conventional percutaneous cordotomy with X-ray visualisation is a much less invasive procedure, allowing safe unilateral operations at the high cervical level, but bilateral lesions high in the cervical spinal cord involving the anterior portion of the lateral spinothalamic tract have been associated with sleep-induced apnoea due to bilateral destruction of the ventrolateral reticulospinal tract [16,17,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Kanpolat et al [10,29,30] described more than 200 patients with intractable pain with pulmonary carcinoma, mesothelioma and Pancoast tumours, and Yequl et al [15] described CT-guided percutaneous cordotomy as a useful procedure for the treatment of severe unilateral cancer pain syndromes. Conventional percutaneous cordotomy with X-ray visualisation is a much less invasive procedure, allowing safe unilateral operations at the high cervical level, but bilateral lesions high in the cervical spinal cord involving the anterior portion of the lateral spinothalamic tract have been associated with sleep-induced apnoea due to bilateral destruction of the ventrolateral reticulospinal tract [16,17,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, Price et al reported that (2,12,28). We observed none of these complications in our series.…”
Section: █ Discussionmentioning
confidence: 99%
“…The surgical procedure was performed as described before by Kanpolat et al (5,6,8,12). The procedure was performed in a computed tomography unit.…”
Section: Ct-guided Hpscc Techniquementioning
confidence: 99%
See 2 more Smart Citations